Concomitant Surgical Ablation for Treatment of Atrial Fibrillation in Patients Undergoing Minimally Invasive Mitral Valve Surgery: A Single-Center Experience in Vietnam - Chuong, Pham Tran Viet; Thuan, Phan Quang; Thanh, Vu Tri; Dinh, Nguyen Hoang (The Thoracic and Cardiovascular Surgeon, 2024)
This study presents the early and midterm outcomes of combining atrial fibrillation (AF) treatment with minimally invasive mitral valve surgery (MIMVS) at our center.From January 2017 to June 2022, our center treated a total of 86 patients with both MIMVS and surgical AF ablation. The patient cohort included 62 women (72.1%) and 24 men (27.9%). The average EuroScore II was 2.64 ± 1.49%, and the patients were followed up for an average period of 46.31 ± 9.84 months.Postoperatively, 95.3% of patients experienced a change in sinus rhythm, and 86.2% were discharged in sinus rhythm. The hospital's mortality rate was 2.3%, with a late mortality rate of 3.5%. Survival analysis revealed an atrial fibrillation–free 5-year follow-up rate of 59.1 ± 9.1%. The 5-year survival rate was 92.7 ± 3.3%.Our 5-year experience demonstrates that the combination of MIMVS and surgical AF ablation can be routinely performed with favorable peri- and postoperative outcomes. This reflects our hospital's culture and guidance on patient selection, particularly when adopting minimally invasive approaches for multiple procedures.
Keywords: atrial fibrillation; ablation surgery; minimally invasive mitral valve surgery; hospital culture